2011
DOI: 10.1186/1476-511x-10-184
|View full text |Cite
|
Sign up to set email alerts
|

Dietary saturated and monounsaturated fats protect against acute acetaminophen hepatotoxicity by altering fatty acid composition of liver microsomal membrane in rats

Abstract: BackgroundDietary polyunsaturated fats increase liver injury in response to ethanol feeding. We evaluated the effect of dietary corn oil (CO), olive oil (OO), and beef tallow (BT) on fatty acid composition of liver microsomal membrane and acute acetaminophen hepatotoxicity.MethodsMale Sprague-Dawley rats were fed 15% (wt/wt) CO, OO or BT for 6 weeks. After treatment with acetaminophen (600 mg/kg), samples of plasma and liver were taken for analyses of the fatty acid composition and toxicity.ResultsTreatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The whale blubber used as a source of contaminants in the present study contains a much higher amount of PUFAs than pork lard, so interpretation of differences between treatment groups in CYP activity should be made with caution. However, because PUFAs have not been found to cause an induction of these enzymes per se [39], we suggest that the findings of induced CYP activities in OC-contaminated fox to be caused by the contaminant load and not the result of differences between treatments in the lipid composition of their diet.…”
Section: Liver Cyp Enzyme Activitiesmentioning
confidence: 79%
See 1 more Smart Citation
“…The whale blubber used as a source of contaminants in the present study contains a much higher amount of PUFAs than pork lard, so interpretation of differences between treatment groups in CYP activity should be made with caution. However, because PUFAs have not been found to cause an induction of these enzymes per se [39], we suggest that the findings of induced CYP activities in OC-contaminated fox to be caused by the contaminant load and not the result of differences between treatments in the lipid composition of their diet.…”
Section: Liver Cyp Enzyme Activitiesmentioning
confidence: 79%
“…It has previously been shown that a high dietary content of polyunsaturated fatty acids (PUFAs) may enhance the induction of CYP enzymes after an animal is exposed to an inducer but that a diet rich in PUFAs does not have an influence on the baseline levels (without inducer) [39]. The whale blubber used as a source of contaminants in the present study contains a much higher amount of PUFAs than pork lard, so interpretation of differences between treatment groups in CYP activity should be made with caution.…”
Section: Liver Cyp Enzyme Activitiesmentioning
confidence: 99%
“…The reduced n -6/ n -3 ratio found in both study groups could be related to reduced hepatic steatosis. In addition, an elevated n -6/ n -3 ratio is associated with attenuated lipid oxidation and secretion and increased lipid accumulation in the liver [ 41 , 42 ]. Even more, PUFAs can be enzymatically released from membrane phospholipids [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…OA prevented excessive production of ROS during sepsis. Mice receiving an olive oil-rich diet had lower levels of MDA in a model of oxidative stress caused by injection of acetaminophen [ 69 ]. Upregulation of UCP2 has been suggested to be a protective mechanism against excessive lipid exposure and the associated increase in ROS production, lending further support to the role of UCP2 as an antioxidative agent [ 70 ].…”
Section: Discussionmentioning
confidence: 99%